2011
DOI: 10.1111/j.1440-1789.2010.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial loss of parvalbumin-containing hippocampal interneurons in dementia with Lewy bodies

Abstract: Dementia with Lewy bodies (DLB) is the second most common neurodegenerative dementia. Among many other neuropathological changes in DLB, brain region-specific cellular deficits have been reported. They include decreases in motor neuron and pyramidal cell densities, while neocortical parvalbumin (parv)-containing neurons are thought to be free of Lewy bodies and spared in DLB. However, elevated parv levels are found in the cerebrospinal fluid of patients suffering from dementia with Lewy bodies. We performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
(55 reference statements)
2
17
1
Order By: Relevance
“…A previous study suggested that Lewy pathology in the hippocampus is harbored in local interneurons, at least in the case of PDD (Flores-Cuadrado et al, 2016). However, no such colocalization was observed in our study (data not shown), and only very little was found in another study focusing on DLB (Bernstein et al, 2011). Early work examining neuronal subtypes containing LBs in temporal cortex revealed that the majority localized to pyramidal cells and not interneurons positive for parvalbumin (Wakabayashi et al, 1995).…”
Section: Discussioncontrasting
confidence: 46%
“…A previous study suggested that Lewy pathology in the hippocampus is harbored in local interneurons, at least in the case of PDD (Flores-Cuadrado et al, 2016). However, no such colocalization was observed in our study (data not shown), and only very little was found in another study focusing on DLB (Bernstein et al, 2011). Early work examining neuronal subtypes containing LBs in temporal cortex revealed that the majority localized to pyramidal cells and not interneurons positive for parvalbumin (Wakabayashi et al, 1995).…”
Section: Discussioncontrasting
confidence: 46%
“…2A), as expected. In the CA1 region of the hippocampus, the flow fractionator identified a loss of neurons, specifically in LBD-DLB (Table 2), that was not observed using microscopically guided sampling by us or others (Bernstein et al, 2011;Joelving et al, 2006). The nearby presubiculum region of the hippocampus has neuronal cell loss of a similar magnitude to AD in LBD-DLB (Harding et al, 2002), and contamination of the samples with this region is likely to explain our results and will always be a difficulty with the isolation of anatomically complex structures for flow fractionator studies.…”
Section: Discussionmentioning
confidence: 76%
“…The results described here are of crucial importance to unravel the role of interneurons in the physiopathology of ALS, because 1) a substantial proportion of ALS patients suffers from cognitive impairments, with concomitant hippocampal damage (Abdulla et al, 2014) and display increased anxiety (Kurt et al, 2007); 2) PV expression is altered in several brain regions of ALS patients (Hayashi et al, 2013) and in presymptomatic mSOD1 mice, and these mice also display an increased number of cortical PVi (Sasaki et al, 2006;Minciacchi et al, 2009); 3) hippocampal PVi are damaged in several disorders, including forms of dementia (Mar ın, 2012;Bernstein et al, 2011); 4) PV overexpression in motor neurons delays disease onset and prolongs survival in mSOD1 (Beers et al, 2001); and 5) PVi are necessary for gamma oscillations (Sohal et al, 2009), are crucial for hippocampus-dependent and hippocampusindependent learning Donato et al, 2013), and are involved in the control of anxiety (Hale et al, 2010). Importantly, the hippocampal PVi loss supports and extends previous findings on regional selectivity of PVi alterations in mSOD1 mice ).…”
Section: Discussionmentioning
confidence: 98%